Patterning and compartment formation in the diencephalon - chatterjee, mallika; LI, JAMES Y. (Frontiers in Neuroscience, 2012)
The diencephalon gives rise to structures that play an important role in connecting the anterior forebrain with the rest of the central nervous system. The thalamus is the major diencephalic derivative that functions as a relay station between the cortex and other lower order sensory systems. Almost two decades ago, neuromeric/prosomeric models were proposed describing the subdivision and potential segmentation of the diencephalon. Unlike the laminar structure of the cortex, the diencephalon is progressively divided into distinct functional compartments consisting principally of thalamus, epithalamus and pretectum. Neurons generated within these domains further aggregate to form clusters called nuclei, which form specific structural and functional units. We review the recent advances in understanding the genetic mechanisms that are involved in the patterning and compartment formation of the diencephalon.